Exercise training in pulmonary rehabilitation: are functional exercises and elastic resistance training effective strategies? - Lima, Fabiano Francisco de [UNESP] (2021)
A key priority in Pulmonary Rehabilitation (PR) programs is to increase their accessibility. Elastic resistance training stands out for its low cost, practicality, and portability, allowing people to perform resistance training in their home environment. Lemgruber® Elastic tubing (LET) has been proposed as a tool for such an end. Exercise training in PR programs commonly involves aerobic and resistance training, showing clinically relevant results when combined. PR programs provide significant functional gains for patients with Chronic Obstructive Pulmonary Disease (COPD). The evidence for increasing physical activity in daily life (PADL) with PR is contradictory and inconsistent. It is suggested an small effect on PADL with an inconsistent translation of functional gains into increased PADL. Functional exercise training can be a promising alternative. Objectives: This thesis presents the following objectives: To assess the length-resistance relation of elongation and resistance of five Lemgruber® elastic tubings (LET) of different diameters; Conduct a systematic review to investigate the effectiveness of elastic resistance training on improving muscle strength, functional exercise capacity, health-related quality of life (HRQoL) and dyspnea in patients with stable COPD; To evaluate the short term (8 weeks) and sustained effects (12 weeks post-training follow-up) of the combination of a functional exercise training, with a training program consisting of aerobic and resistance exercise in patients with COPD. Methods: Four studies were conducted to answer the objectives of this thesis and are presented as separated articles: 1) a descriptive laboratory study to evaluate the LET; 2) a systematic review and meta- analysis on the effectiveness of elastic resistance training in patients with COPD; 3) a study protocol and a randomized clinical trial on the effects of the combination of functional exercises with exercise training in patients with COPD. Results: The main viiifindings of this thesis were that the large array of resistances delivered by LET, along with its safety and reasonable estimation of reference values, support its use in clinical practice. Elastic resistance training is an effective intervention to improve muscle strength in patients with COPD. Further, compared to resistance training using weight machines, elastic resistance training demonstrated similar effects on muscle strength, functional exercise capacity, HRQoL and dyspnea. The inclusion of a functional exercise training protocol in training conventionally performed by patients with COPD could not improve the PADL and activities in daily living limitations.